The idea of a Turkish world from the Adriatic to the wall of China: Relations between Turkey and the Turkic Republics during the 1990s - Sert, Hüseyin. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This thesis scrutinizes the reaction of Turkey towards the emergence of the Turkic Republics in the Post-Cold War Period. In doing this, it does seek not only to give an account of Turkish foreign policy towards the Turkic Republics, but also to illustrate the reactions of the Turkish public opinion, especially of the Turkish nationalists and the impact of this reaction on the foreign policy agenda of Turkey. In this regard, this study departs from a classical foreign policy analysis perspective since it takes the domestic politics issues such as national identity and common culture into a foreign policy analysis. By making such an analysis, this study has found out that, Turkey’s enthusiastic interest in the emergence of the Turkic Republics was stemmed from some historical and conjunctural reasons. These reasons led Turkey to pursue an active policy towards the region in a way surpassing its potential. On the other hand, the Turkic republics, with the exception of Azerbaijan during the initial years of its independence, did not respond Turkey’s enthusiasm at the same degree. Turkey’s failure to see the region as a monolithic bloc also hindered the development of cooperation. In short, Turkey’s misperceptions prevented Turkey from becoming influential in the politics of Central Asia as it predicted at the beginning. At the end of the decade, neither Turkey was the leader of the Turkic World nor was the Turkic world was a region having a vital significance for Turkish foreign policy.
Keywords: Turkic peoples.